PENDAMPINGAN PEMBUATAN DAN PENGELOLAAN DATA ELEKTRONIK JEMAAT GKJ WATES - Yetli Oslan; Harianto Kristanto; Raden Gunawan Santosa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2021)
Church parishioners data management is an important part of the administration of a church. In fact, many churches do it manually where parishionersal data is stored in physical forms or in church record books. This condition happened at GKJ Wates. The initial condition at GKJ Wates is the data from of a physical form . The data is the result of the census about 2 (two) years ago. It is realized that the data has changed a lot, so it is necessary to update before implementing electronic data management. In an effort to assist the administration of the church's data, assistance steps have been developed that include the compilation of attributes relevant to the church's data management. Furthermore, the attributes are compiled into a form that is ready to be filled out by each parishioners. This agreed form is then distributed to the parishioners through their respective district administrators. The church team, assisted by the UKDW PkM team, recorded the parishioners's data electronically, complete with a spiritual journey scheme including baptism, sidi, and marriage. By utilizing Excel Macro, the electrical data of the GKJ Wates parishioners was successfully visualized in the form of a dashboard. The visualized parishioners data includes the percentage of the parishioners by blood type and gender, the church's spiritual journey scheme based on membership category, membership records, age category, and gender. The information on this dashboard can help the church in making decisions related to the development of the parishioners at GKJ Wates.